2021
DOI: 10.1080/23311975.2021.1938349
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility and firm performance: The moderation of investment horizon and corporate governance

Abstract: The current study proposes an integrated theoretical frame work, to explain the moderating role of institutional investors, their investment horizon and corporate governance mechanism in the sustainability of corporate social responsibility (CSR) and firm's performance nexus. The proposed model explains how, the positive association between CSR and firm performance relationship, established on the basis of the stakeholder and corporate citizenship theories, can be further strengthened (effective monitoring hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 85 publications
0
7
0
Order By: Relevance
“…Regarding foreign IO, Lu and Abeysekera (2021) found no moderator influence on the link between CSR reporting and cumulative abnormal returns in a Chinese setting. One study also relied on the IO type (Waheed et al, 2021) in Pakistan and stressed the moderating impact of pension funds on the positive impact of social contribution value per share on Tobin's Q.…”
Section: Findings Of the Literature Reviewmentioning
confidence: 99%
“…Regarding foreign IO, Lu and Abeysekera (2021) found no moderator influence on the link between CSR reporting and cumulative abnormal returns in a Chinese setting. One study also relied on the IO type (Waheed et al, 2021) in Pakistan and stressed the moderating impact of pension funds on the positive impact of social contribution value per share on Tobin's Q.…”
Section: Findings Of the Literature Reviewmentioning
confidence: 99%
“…Few studies also document that companies that spend and support more on CSR activities pay off better when the companies have a better relationship with employees and shareholders (Freeman, 2010; Hansen et al, 2011; Porter & Kramer, 2002). Followed by, Waheed et al (2021) confirm that corporate social responsibility positively influences the firm performance. On the contrary, Jones (1991), Fatemi et al (2017), Lee and Park (2009), Nollet et al (2016), Orlitzky and Benjamin (2001), and Waddock and Graves (1997) document that CSR spending adversely affects the firms' financial performance.…”
Section: Introductionmentioning
confidence: 94%
“…Many research works have focused on the CSR-financial performance nexus, while evidence is inconclusive. Most prior studies have concluded that the higher a firm performs in CSR, the better its financial performance will be (Franco et al , 2020; Kammoun et al , 2021; Waheed et al , 2021). In this vein, Hou (2019) found that socially responsible firms benefit from superior financial performance compared to companies that do not adopt CSR initiatives.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%